Transposable Elements as Stress Adaptive Capacitors Induce Genomic Instability in Fungal Pathogen Magnaporthe oryzae - Chadha, Sonia (Public Library of Science, 2014)

(untitled)
A fundamental problem in fungal pathogenesis is to elucidate the evolutionary forces responsible for genomic rearrangements leading to races with fitter genotypes. Understanding the adaptive evolutionary mechanisms requires identification of genomic components and environmental factors reshaping the genome of fungal pathogens to adapt. Herein, Magnaporthe oryzae, a model fungal plant pathogen is used to demonstrate the impact of environmental cues on transposable elements (TE) based genome dynamics. For heat shock and copper stress exposed samples, eight TEs belonging to class I and II family were employed to obtain DNA profiles. Stress induced mutant bands showed a positive correlation with dose/duration of stress and provided evidences of TEs role in stress adaptiveness. Further, we demonstrate that genome dynamics differ for the type/family of TEs upon stress exposition and previous reports of stress induced MAGGY transposition has underestimated the role of TEs in M. oryzae. Here, we identified Pyret, MAGGY, Pot3, MINE, Mg-SINE, Grasshopper and MGLR3 as contributors of high genomic instability in M. oryzae in respective order. Sequencing of mutated bands led to the identification of LTR-retrotransposon sequences within regulatory regions of psuedogenes. DNA transposon Pot3 was identified in the coding regions of chromatin remodelling protein containing tyrosinase copper-binding and PWWP domains. LTR-retrotransposons Pyret and MAGGY are identified as key components responsible for the high genomic instability and perhaps these TEs are utilized by M. oryzae for its acclimatization to adverse environmental conditions. Our results demonstrate how common field stresses change genome dynamics of pathogen and provide perspective to explore the role of TEs in genome adaptability, signalling network and its impact on the virulence of fungal pathogens.